2010
DOI: 10.1016/j.matlet.2010.09.010
|View full text |Cite
|
Sign up to set email alerts
|

A one-step process to engineer superhydrophobic copper surfaces

Abstract: Superhydrophobic surfaces are conventionally prepared employing two steps: roughening a surface and lowering their surface energy. In the present work, a direct voltage (DC) is applied between two copper plates immersed in a dilute ethanolic stearic acid solution. The surface of the anodic copper electrode transforms to superhydrophobic due to a reaction between copper and stearic acid solution. The fabrication process of superhydrophobic copper surfaces is simplified in just one-step.The surface of the anodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(80 citation statements)
references
References 14 publications
6
65
0
1
Order By: Relevance
“…The high angle XRD shows four characteristic peaks of aluminum [18] and the low angle XRD spectrum prove that the thin film is the copper stearate as we reported earlier on copper surfaces [12,19] The characteristic copper stearate peaks are identified by triangular legends in Figure1b. Figure 1c shows the FTIR spectra of chemically cleaned Al substrate and that of the thin films on aluminum surfaces prepared with varying times of 1, 10 and 60 minutes.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…The high angle XRD shows four characteristic peaks of aluminum [18] and the low angle XRD spectrum prove that the thin film is the copper stearate as we reported earlier on copper surfaces [12,19] The characteristic copper stearate peaks are identified by triangular legends in Figure1b. Figure 1c shows the FTIR spectra of chemically cleaned Al substrate and that of the thin films on aluminum surfaces prepared with varying times of 1, 10 and 60 minutes.…”
Section: Introductionsupporting
confidence: 76%
“…Due to the versatile applications of superhydrophobic surfaces researchers all around the world is are continuously working in this field of research [2][3][4][5][6]. Our group is actively working in the fabrication of superhydrophobic surfaces on aluminum and other metal surfaces using different techniques [7][8][9][10][11][12][13][14][15][16][17]. For example, we have previously shown that copper surfaces can be made superhydrophobic by a simple one-step electrochemical process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Creating a rough surface, as well as reducing the surface energy is attributed to the modification of superhydrophobicity [7]. In the last few decades, a large effort has been devoted to the realization of superhydrophobic surfaces, due to their applications in biology [8], anti-corrosion [9][10][11][12], anti-icing [13], self-cleaning [14], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Les superhydrophobes sont souvent utilisés dans le domaine biomédical [9], empêchant les contaminants de se propager sur les surfaces ou encore en augmentant les compatibilités biologique et chimique. De plus la surface peut servir comme agent anticorrosif [10] …”
Section: éQuationunclassified